Dicyphus cerastii: First data on development, survival, and reproduction - Gonçalo Abraços-Duarte; Filipe Madeira; Paula Souto; Elsa Borges da Silva; Elisabete Figueiredo (PLoS ONE, 2025)
Dicyphus cerastii Wagner (Hemiptera: Miridae) is an important predator in horticultural crops. This study provides the first data on biological traits like development, survival, and reproduction for this species. We investigated how host (tomato, tobacco, and Cape gooseberry) and temperature (15.0, 20.0, 25.0 ±  1 °C) influenced nymphal development, survival, and adult longevity. In the absence of prey, nymphs failed to complete development on any host. When prey was available, nymphal development, survival and longevity declined as temperature increased across all hosts. Development and longevity of D. cerastii were further examined on tomato, at seven temperatures (15.0, 20.0, 25.0, 27.5, 30.0, 32.5, 35.0 ±  1°C). Reproductive capacity was measured at 20.0, 25.0, 30.0 ±  1°C, on tomato. Egg development ranged from 30.6 days (15.0 °C) to 9.7 days (32.5 °C). Nymph development decreased from 40.0 days (15.0 °C) to 16.4 days (30.0 °C), and no nymphs completed development above 30.0 °C. The optimal temperature for development from egg to adult was estimated at 29.2 °C., while the minimum threshold for immature development was approximately 7.0 °C. The thermal constant for development was 230.4 degree-days for eggs, and 394.0 degree-days for nymphs. Adult longevity ranged from 158.6 days (15.0 °C) to 13.8 days (30.0 °C). The net reproductive rate (R0) and generation time (T) were highest at 20.0 °C, while the intrinsic rate of increase (rm) was highest at 25.0 °C.